The macroeconomic limits of income's policy in a dependent country : The need and possibilities for radical reforms in social policies in Argentina after the crisis (2001-2008) - Féliz, Mariano (2011)
Fil: Féliz, Mariano. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Instituto de Investigaciones en Humanidades y Ciencias Sociales (UNLP-CONICET); Argentina.